Pengaruh Model Pembelajaran Inkuiri Learning Terhadap Kemampuan Berfikir Kritis dalam Pembelajaran PAI (Tazakka: Jurnal Pendidikan dan Keislaman, 2024)
This research is an experimental study to determine the effect of the inquiry learning model on critical thinking skills. The research design used in this study is the One Group Pretest-Postest Design, the experimentation is only carried out in one group where the group is given a pretest then given treatment then a final test (posttest) is carried out. The groups sampled in this study were 35 students of class VIII E SMPN 1 Sungai Penuh. The instrument used by researchers in this study was obtained from observation (observation), consider (questionnaire) and documentation. The results of the study were: 1) before the application of the inquiry learning model, students lacked critical thinking skills in the learning process, and teachers in the learning process still used conventional learning models. 2) after learning activities using the inquiry learning model, students' critical thinking skills increase, in the learning process students are more active, enthusiastic, and participating so that students can improve their critical thinking skills. Based on the results of the research above, it can be concluded that the inquiry learning model is believed to be able to make students more active, enthusiastic, and participate in the learning process so that students' critical thinking skills increase.
Keywords: Inquiry Learning Model; Students’ Critical Thinking